THE INFLUENCE OF FOOD QUALITY, PRICE FAIRNESS, PRODUCT VARIETY, SERVICESCAPE, STORE BRAND IMAGE ON REPURCHASE INTENTION THROUGH PURCHASE DECISION AND CUSTOMER SATISFACTION OF PIZZA HUT VISITORS IN SAMARINDA CITY - Suramli; St Nurhasanah; Sarwo Eddy Wibowo; Usratul Maqfira (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Food Quality, Price Fairness, Product Variety, Servicescape, and Store Brand Image on Repurchase Intention Mediated by Purchase Decision and Customer Satisfaction among Pizza Hut visitors in Samarinda City. In the increasingly competitive fast food restaurant industry, understanding the factors that drive purchasing decisions and customer satisfaction is crucial to foster customer loyalty. Through a quantitative approach, this study examines marketing variables such as product quality, fair prices, menu diversity, restaurant atmosphere, and brand image that can influence customer decisions and satisfaction which ultimately impact repurchase intentions. The results of this study are expected to provide theoretical contributions in the study of consumer behavior, as well as practical benefits for restaurant managers in developing more effective marketing strategies to retain customers and improve business performance. The results of the study indicate that price fairness, product variety, and store brand image have a significant effect on purchase decisions, while food quality and servicescape have no significant effect on purchase decisions. Furthermore, food quality, price fairness, product variety, and servicescape have a significant effect on customer satisfaction, while store brand image has no significant effect on customer satisfaction. In the final stage of the model, it was found that purchase decisions, customer satisfaction, and servicescape have a significant effect on repurchase intentions, while food quality, price fairness, and product variety have no significant direct effect on repurchase intentions. These findings indicate that purchase decisions and customer satisfaction play an important mediating variable in explaining the formation of Pizza Hut consumers' repurchase intentions.